Immunological dimensions of neuroinflammation and microglial activation: exploring innovative immunomodulatory approaches to mitigate neuroinflammatory progression - Fornari Laurindo, Lucas; Aparecido Dias, Jefferson; Cressoni Araújo, Adriano; Torres Pomini, Karina; Machado Galhardi, Cristiano; Rucco Penteado Detregiachi, Claudia; Santos de Argollo Haber, Luíza; Donizeti Roque, Domingos; Dib Bechara, Marcelo; Vialogo Marques de Castro, Marcela; de Souza Bastos Mazuqueli Pereira, Eliana; José Tofano, Ricardo; et al. (Frontiers in Immunology, 2024)
The increasing life expectancy has led to a higher incidence of age-related neurodegenerative conditions. Within this framework, neuroinflammation emerges as a significant contributing factor. It involves the activation of microglia and astrocytes, leading to the release of pro-inflammatory cytokines and chemokines and the infiltration of peripheral leukocytes into the central nervous system (CNS). These instances result in neuronal damage and neurodegeneration through activated nucleotide-binding domain and leucine-rich repeat containing (NLR) family pyrin domain containing protein 3 (NLRP3) and nuclear factor kappa B (NF-kB) pathways and decreased nuclear factor erythroid 2-related factor 2 (Nrf2) activity. Due to limited effectiveness regarding the inhibition of neuroinflammatory targets using conventional drugs, there is challenging growth in the search for innovative therapies for alleviating neuroinflammation in CNS diseases or even before their onset. Our results indicate that interventions focusing on Interleukin-Driven Immunomodulation, Chemokine (CXC) Receptor Signaling and Expression, Cold Exposure, and Fibrin-Targeted strategies significantly promise to mitigate neuroinflammatory processes. These approaches demonstrate potential anti-neuroinflammatory effects, addressing conditions such as Multiple Sclerosis, Experimental autoimmune encephalomyelitis, Parkinson’s Disease, and Alzheimer's Disease. While the findings are promising, immuno-therapies often face limitations due to Immune-Related Adverse Events. Therefore, the conduction of randomized clinical trials in this matter is mandatory, and will pave the way for a promising future in the development of new medicines with specific therapeutic targets.